Social policy in an era of global competition : from global to local perspectives / edited by Dan Horsfall and John Hudson. - Horsfall, Daniel; Hudson, John, 1972- (Policy Press, 2017)
Providing a new cross-national and international narrative on how global competition has reshaped welfare states, this book captures the complexity of social policy reform process that have taken place over the past twenty-five years.